Remote teaching practices and learning support during COVID-19 lockdowns in Portugal: Were there changes across time? - Alves, Diana; Marques, Sofia; Cruz, Joana; Mendes, Sofia Abreu; Cadime, Irene (Frontiers in Psychology, 2022)
The Covid-19 pandemic challenged countries, regions, schools, and individuals. School closures due to lockdowns forced changes in the teaching practices and the learning support provided to children at home. This study aimed to provide insights on the changes between the first and the second lockdowns in Portugal, concerning remote teaching practices and family support to children’s education. A self-report questionnaire was filled by 144 parents of third grade students. The results show that, between the two lockdowns, there was a significant decrease in the amount of support provided at home to school assignments and activities, as well as in the amount of time spent by students in TV broadcasted lessons and in reading training supported by the family. Inversely, families reported a significant increase in the amount of time spent by students in independent reading activities and in the time spent in training reading guided by teachers. The number of synchronous lessons with a teacher and the number of times students trained reading during a synchronous lesson also increased in the second lockdown. Additionally, in the second lockdown, parents perceived synchronous lessons to be more effective at improving their child’s reading skills and perceived themselves as more capable of supporting their child in reading acquisition. These findings are used to discuss school responses and remote teaching and learning practices during the Covid-19 pandemic.